2007
DOI: 10.1071/bt06032
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchies of cause: understanding rarity in an endemic shrub Verticordia staminosa (Myrtaceae) with a highly restricted distribution

Abstract: Verticordia staminosa C.Gardner & A.C.George subsp. staminosa is an extremely rare shrub occurring as an isolated population of ~1200 plants on a granite outcrop in the semi-arid agricultural region of Western Australia, separated from its closest relative V. staminosa subsp. cylindracea by 400 km. We aimed to determine a hierarchy of causes for explaining the extremely restricted distribution of subsp. staminosa, and to determine the genetic relationships among populations within both subspecies. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…The degree of genetic structure at Jasper Hill may be influenced by the effects of genetic drift under a scenario of limited pollen production and dispersal among populations of smaller effective size Despite the suitability of inselberg habitats for studies assessing genetic connectivity and the occurrence of inselberg habitat around the world, detailed studies of endemic inselberg flora are limited. Species occurring on granite outcrops in WA have shown higher levels of genetic differentiation than observed in A. woodmaniorum, for example, Eucalyptus caesia (Byrne and Hopper, 2008) and Verticordia staminosa subspecies cylindacea (Yates et al, 2007). Populations of these species are distributed over wider geographical ranges and have greater levels of geographic isolation however.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The degree of genetic structure at Jasper Hill may be influenced by the effects of genetic drift under a scenario of limited pollen production and dispersal among populations of smaller effective size Despite the suitability of inselberg habitats for studies assessing genetic connectivity and the occurrence of inselberg habitat around the world, detailed studies of endemic inselberg flora are limited. Species occurring on granite outcrops in WA have shown higher levels of genetic differentiation than observed in A. woodmaniorum, for example, Eucalyptus caesia (Byrne and Hopper, 2008) and Verticordia staminosa subspecies cylindacea (Yates et al, 2007). Populations of these species are distributed over wider geographical ranges and have greater levels of geographic isolation however.…”
Section: Discussionmentioning
confidence: 94%
“…For these species, the surrounding landscape typically comprises a matrix of unsuitable habitat that acts as an effective physical barrier to dispersal and the size and spatial arrangement of populations assumes an important role in the structuring and maintenance of genetic diversity. Limitations to connectivity result in a degree of demographic isolation and genetic isolation among populations (Slatkin, 1987), and produce the phylogeographic and genetic structuring observed in many habitat specific, rare, endemics (Yates et al, 2007;Byrne and Hopper, 2008;Butcher et al, 2009). Limited connectivity among disjunct populations can result in reduced levels of genetic diversity as a result of increased levels of inbreeding and via the negative impacts of genetic drift (Slatkin, 1987;Ellstrand, 1992), both of which are further enhanced in small populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear vegetation gradient from herbaceous campo rupestre to montane forest accompanying the gradient of soil depth: herbaceous campo rupestre<shrubby campo rupestre<capão forest<montane forest. Yates et al (2011b) similarly identified species habitat preferences associated with soil depth for bandediron plant communities in Western Australia.…”
Section: Discussionmentioning
confidence: 97%
“…This pattern of species becoming 'stranded' on rock outcrops has been documented elsewhere in Australia (Gibson et al 2012). Genetic studies could shed more light on the relative period of historical separation between populations (Yates et al 2007). …”
Section: Goodenia Atriplexifolia and Sida Asterocalyx)mentioning
confidence: 99%